Akibat Hukum Wanprestasi dalam Perjanjian Waralaba (Franchise) Pempek Farina di Kota Denpasar - Kenneth De Lara Lim; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2020)
Franchise is a business relationship between a brand owner and another party that gives permission for the use of the mark within a certain period. If the parties do not comply with the contents of the franchise agreement, the injured party can sue. The franchise operating in Denpasar is Pempek Farina. Pempek Farina is a franchise business that is engaged in the fast food industry. The purpose of this study is to describe the form of the Pempek Farina franchise agreement in Denpasar and analyze the legal consequences for the franchisee if it violates the Pempek Farina franchise agreement. The purpose of this study is to determine the form of the agreement and determine the legal consequences for the franchisee if it violates the franchise agreement. The research method used is empirical research with a sociological approach. The results showed that the form of the Pempek Farina franchise agreement is a form of underhand agreement, the result of which arises when the franchisee defaults on the agreement, the agreement that has been made may expire. With the provisions of Article 1266 and Article 1267 of the Criminal Code the franchisor will cancel the agreement and ask the franchisee to stop selling the product of the franchisor.